Changes in medical student and doctor attitudes toward older adults after an intervention: a systematic review - Samra, Rajvinder; Griffiths, Amanda; Cox, Tom; Conroy, Simon; Knight, Alec (Wiley, 2013)
Research investigating the effects of attitude-focused interventions on doctors' and medical students' attitudes toward older adults has produced mixed results. The objective of this systematic review was to determine whether factors pertaining to study design and quality might provide some explanation of this inconclusive picture. Articles were judged of interest if they reported doctors' or medicals students' attitude scores before and after a geriatric-focused intervention. Articles that did not report the measure used, mean scores, or inferential statistics were excluded. Twenty-seven databases, including Medline, PsychInfo, and Embase, were searched through April 2011 using a systematic search strategy. After assessment and extraction, 27 studies met the eligibility criteria for this review. These studies demonstrated inconsistent results; 14 appeared successful in effecting positive attitude change toward older adults after an intervention, and 13 appeared unsuccessful. Attitude change results differed in line with the content of the intervention. Of the 27 studies, 11 interventions contained solely knowledge-building content. Three of these studies demonstrated positive changes in doctors' or medical students' attitudes toward older adults after the intervention. The remaining 16 interventions incorporated an empathy-building component, such as an aging simulation exercise or contact with a healthy older adult. Of these, 11 successfully demonstrated positive attitude change after the intervention. The inclusion of an empathy-building task in an intervention appears to be associated with positive attitude change in medical students' and doctors' attitudes toward older adults.